Reproductive Organ Profile of Pullet Phase Kampung Chicken After L-Isoleucine Supplementation in Feed - Lisnahan, Charles Venirius; Elu, Maria Eriska; Dethan, Agustinus Agung; Nubatonis, Alfred (Journal of Tropical Animal Science and Technology, 2024)
The aim of this research was to determine the effect of supplementation of L-isoleucine in feed on the reproductive organ profile of Native chickens at the pullet phase. This research was carried out from April to July 2023 at Sasi Village, Kota Kefamenanu Sub-District, North Central Timor Regency. A total of 100 Native chickens aged 6 weeks with an average weight of 400 g were used in this study. The research method used was a Completely Randomized Design (CRD) consisting of 5 treatments and 5 replications. Each replication consisted of 4 Native chickens. The treatments given were T0 (feed without L-isoleucine), T1 (T0 + 0.05% L-isoleucine), T2 (T0 + 0.15% L-isoleucine), T3 (T0 + 0.25% L-isoleucine), and T4 (T0 + 0.35% L-isoleucine). The variables observed were the weight of the ovaries, the distance between the 2 pubic bones, the distance between the pubic bone and the sternum, testicular weight and testicular volume. The data obtained were analyzed using analysis of variance and Duncan's test. The results showed that the ovarian weight for T0, T1, T2, and T3 and T4 were 1.14 ± 0.18; 1.43±0.12; 2.26±0.53; 1.76 ± 0.34 and 1.33 ± 0.27 g/head, respectively. The distance between the 2 pubic bones were 21.04 ± 0.49; 22.70±0.61; 25.40±0.82; 23.90 ± 0.46 and 22.08 ± 0.63 mm/head, respectively. The distance between the pubic bone and the sternum were 31.82 ± 1.93; 33.60±1.10; 37.04±2.36; 33.76 ± 1.27 and 31.56 ± 0.93 mm/head, respectively. Testicular weight were 5.56 ± 0.42; 6.15±1.48; 7.58±0.47; 6.80 ± 0.43 and 6.16 ± 0.40 g/head, respectively. Testicular volume were 5.04 ± 0.55; 5.82±0.41; 7.14 ± 0.50; 6.58 ± 0.47 and 6.06 ± 0.28 mL/head, respectively. Statistical analysis showed that treatment had a significant effect on ovary weight, the distance between the 2 pubic bones, the distance between the pubic bone and the sternum, testicular weight and testicular volume in Kampung chickens (P<0.05). It was concluded that the use of 0.15% L-isoleucine in feed gave the best results on ovary weight, distance between 2 pubic bones, distance between pubic bone and breast bone, testicular weight and testicular volume in pullet phase Native chickens.